Pengaruh Kesadaran Wajib Pajak, Pengetahuan Perpajakan dan Kualitas Pelayanan Fiskus Terhadap Kepatuhan Wajib Pajak dalam Membayar Pajak Hotel di Kabupaten Buleleng - Putra, Kadek Vanny Panji; Sujana, Edy (Jurnal Akuntansi Profesi, 2021)
This study aims to determine the effect of taxpayer awareness on taxpayer compliance, tax knowledge on taxpayer compliance, and the fiscus service quality on taxpayer compliance. This research is a quantitative research with the number of respondents as many as 35 employees of the financial division of hotels in Buleleng Regency. Data obtained by distributing questionnaires directly. The sample technique used is purposive sampling. The data used are primary data in the form of respondents' answers and processed using SPSS 20 for windows. The results showed that taxpayer awareness had a positive and significant effect on taxpayer compliance, tax knowledge had a positive and significant effect on taxpayer compliance and fiscus service quality had a positive and significant effect on taxpayer compliance.